The Evaluation of the Effects of Cochlear Implant Treatment on Quality of Life and Costs: A Systematic Review - Kocas, Meryem; Yigit, Arzu (Iranian Scientific Society Medical Entomology, 2026)
Background: We aimed to systematically examine the effects of Cochlear Implant Treatment (CIT) on quality of life and costs and to raise awareness of its economic and clinical value. Methods: A systematic scan was conducted for relevant published studies over Google Scholar, PubMed, ScienceDirect, Springer Link, and Web of Science electronic databases. The search covered studies published between January 2009 and December 2024. Literature search and data extraction were conducted by two researchers and the Drummond Checklist was used to assess the risk of bias and applicability of the included literature. The study was conducted following the PRISMA-2020 guidelines. Results: Overall, 11 studies were included in the study. When these studies were evaluated, it was found that most of them were conducted in 2021, children were the most preferred sample group, and these studies focused on unilateral Cochlear Implant Treatment. The lowest quality of life value was 0.452 and the highest was 0.93. Cost-effectiveness analyses were used in the studies to determine the cost-effectiveness of cochlear implants, and the Markov Model was preferred. The Incremental Cost-Effectiveness Ratio (ICER) was employed as the outcome measure highly cost-effective in lower-income settings such as Taiwan, while higher ICER values were observed in high-income countries such as the USA. Conclusion: Cochlear implant treatment improves quality of life and is generally cost-effective for both children and adults, as supported by the majority of studies.
Keywords: Hearing Loss; Cochlear Implant; Quality Of Life; Cost-Effectiveness; Systematic Review